Myopia progression control lens reverses induced myopia in chicks. (26th July 2017) - Irving, Elizabeth L.; Yakobchuk‐Stanger, Cristina
Abstract: Purpose: To determine whether lens induced myopia in chicks can be reversed or reduced by wearing myopia progression control lenses of the same nominal (central) power but different peripheral designs. Methods: Newly hatched chicks wore −10D Conventional lenses unilaterally for 7 days. The myopic chicks were then randomly divided into three groups: one fitted with Type 1 myopia progression control lenses, the second with Type 2 myopia progression control lenses and the third continued to wear Conventional lenses for seven more days. All lenses had −10D central power, but Type 1 and Type 2 lenses had differing peripheral designs; +2.75D and +1.32D power rise at pupil edge, respectively. Axial length and refractive error were measured on Days 0, 7 and 14. Analyses were performed on the mean differences between treated and untreated eyes. Results: Refractive error and axial length differences between treated and untreated eyes were insignificant on Day 0. On Day 7 treated eyes were longer (T1; 0.44 ± 0.07 mm, T2; 0.27 ± 0.06 mm, C; 0.40 ± 0.06 mm) and more myopic (T1; −9.61 ± 0.52D, T2; −9.57 ± 0.61D, C; −9.50 ± 0.58D) than untreated eyes with no significant differences between treatment groups. On Day 14 myopia was reversed (+2.91 ± 1.08D), reduced (−3.83 ± 0.94D) or insignificantly increased (−11.89 ± 0.79D) in treated eyes of Type 1, Type 2 and Conventional treated chicks respectively. Relative changes in axial lengths (T1; −0.13 ± 0.09 mm, T2; 0.36 ± 0.09 mm, C; 0.56 ± 0.05 mm) were consistent with changes in refraction. Refractive error differences were significant for all group comparisons ( p < 0.001). Type 1 length differences were significantly different from Conventional and Type 2 groups ( p < 0.001). Conclusions: Myopia progression control lens designs can reverse lens‐induced myopia in chicks. The effect is primarily due to axial length changes. Different lens designs produce different effects indicating that lens design is important in modifying refractive error.